(untitled) (Global Journal of Medical Research, 2022)
As a starting point, it should be noted that the early Hungarian regulations were rather unchiseled. It is well known that the institutional care of the sick, the poor was first dealt with by the clergy and monastic orders. 1 The Benedictine order settled by King St. Stephen (ruler 1000-1038) in particular can be highlighted, as they - as a primary healing order - maintained a hospital in Pannonhalma, in the area of the abbey, as early as 1221. 2 In addition to all this, one of the decrees of King Kalman (ruler 1095-1116) is probably the first piece of health legislation. It clearly states, "Women who have lost their fetuses should atone to the principal."